Handbook of Nanomaterials and Nanocomposites for Energy and Environmental Applications 2020
DOI: 10.1007/978-3-030-11155-7_149-1
|View full text |Cite
|
Sign up to set email alerts
|

Development of Bio-Based and Biodegradable Plastics

Abstract: The impact of environmental-related issues poses a deleterious effect on the existence of human life and its biophysical surroundings. Discarded plastic materials have been identified as threats to the environment as most of these

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 100 publications
0
8
0
Order By: Relevance
“…Polyhydroxyalkanoates (PHAs) are a class of biodegradable and renewable polymers which can be produced by various bacteria as an energy reserve, ensuring the long-term survival of the bacteria during nutrient-scarce conditions. , These bio-based polymers are considered as green polymers of the future due to their potential to replace conventional polymers . It has been shown that the bacteria can yield high-quality PHAs using pure substrates and sterile conditions, but under these expensive growth conditions, the polymers are not economically competitive with the conventional polymers . Alternatively, it is possible to apply an open mixed microbial culture (MMC) to produce low-cost PHAs.…”
Section: Introductionmentioning
confidence: 99%
“…Polyhydroxyalkanoates (PHAs) are a class of biodegradable and renewable polymers which can be produced by various bacteria as an energy reserve, ensuring the long-term survival of the bacteria during nutrient-scarce conditions. , These bio-based polymers are considered as green polymers of the future due to their potential to replace conventional polymers . It has been shown that the bacteria can yield high-quality PHAs using pure substrates and sterile conditions, but under these expensive growth conditions, the polymers are not economically competitive with the conventional polymers . Alternatively, it is possible to apply an open mixed microbial culture (MMC) to produce low-cost PHAs.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, packaging protects food products from physical, chemical, and microbiological harm by enabling the handling, transportation, and storage of various food products, resulting in improved quality preservation and shelf-life [3,4]. However, petroleum-based polymeric materials, sometimes known as plastic, are the most employed in food packaging [5]. Plastic packaging has limitations in terms of biodegradability, recyclability, biocompatibility, and reusability [5].…”
Section: Introductionmentioning
confidence: 99%
“…However, petroleum-based polymeric materials, sometimes known as plastic, are the most employed in food packaging [5]. Plastic packaging has limitations in terms of biodegradability, recyclability, biocompatibility, and reusability [5]. These restrictions on plastic packaging produce a massive amount of garbage, causing serious environmental difficulties such as soil contamination, marine pollution, air pollution, and animal deaths around the world [5,6].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations